Gelatins from three cultured freshwater fish skins obtained by liming process - Bakar, Jamilah; Tan, K. W.; Mohamad Razali, Umi Hartina; A., Azizah (Elsevier, 2011)
The physico-chemical properties of gelatins from the skins of Red tilapia (Oreochromis nilotica), Walking catfish (Clarias batrachus) and Striped catfish (Pangasius sutchi fowler) obtained through a liming process for 14 days were evaluated. All the gelatins had very mild to undetectable fishy odour and had acceptable colour attributes, which were light yellowish to whitish. The highest gelatin yield (dry basis) was obtained from red tilapia (39.97%) skin and the bloom strength exceeded 300 g. The pH values of the gelatins were in the vicinity of 5.0. The viscosity (cp) was highest in striped catfish, followed by red tilapia and walking catfish. Their melting points were in the vicinity of 26 ± 1 °C. Turbidity was lowest in the red tilapia gelatin. Glycine, proline and alanine were the three highest amino acids found in all the gelatins obtained.